The air campaign planning for combat - Warden, John A. 1943- (National Defense University Press Publications, 1988)
In the short history of air warfare, no nation with superior air forces has ever lost a war to the force of enemy arms. Air superiority by itself, however, no longer guarantees victory. This book, one of the first analyses of the pure art of planning the aerial dimension of war, explores the complicated connection between air superiority and victory in war. In The Air Campaign, Colonel John A. Warden III focuses on the use of air forces at the operational level in a theater of war. The most compelling task for the theater commander, he argues, is translating national war objectives into tactical plans at operational levels. He presents his case by drawing on fascinating historical examples, stressing that the mastery of operational-level strategy can be the key to winning future wars. Colonel Warden shows us how to use air power more effectively-through rough mass, concentration, and economy of forces-because, he warns, the United States no longer holds an edge in manpower, production capacity, and technology. Simply put, an air force inferior in numbers must fight better and smarter to win. This book offers planners greater understanding of how to use air power for future air campaigns against a wide variety of enemy capabilities in a wide variety of air operations. As the reader will see, the classic principles of war also apply to air combat. One of the author's important contributions is to demonstrate that perception to those whose grave responsibility one day may be to plan and carry through a victorious air campaign